Effects of High Altitude on Sleep and Respiratory System and Theirs Adaptations - Turhan San; Senol Polat; Cemal Cingi; Gorkem Eskiizmir; Fatih Oghan; Burak Cakir (The Scientific World Journal)
High-altitude (HA) environments have adverse effects on the normal functioning body of people accustomed to living at low altitudes because of the change in barometric pressure which causes decrease in the amount of oxygen leading to hypobaric hypoxia. Sustained exposure to hypoxia has adverse effects on body weight, muscle structure and exercise capacity, mental functioning, and sleep quality. The most important step of acclimatization is the hyperventilation which is achieved by hypoxic ventilatory response of the peripheral chemoreceptors. Hyperventilation results in increase in arterial carbondioxide concentration. Altitude also affects sleep and cardiac output, which is the other determinant of oxygen delivery. Upon initial exposure to HA, the resting pulse rate increases rapidly, but with acclimatization, heart rate and cardiac output tend to fall. Another important component that leads to decrease in cardiac output is the reduction in the stroke volume with acclimatization. During sleep at HA, the levels of CO2 in the blood can drop very low and this can switch off the drive to breathe. Only after the body senses a further drop in O2 levels breathing is started again. Periodic breathing is thought to result from instability in the control system through the hypoxic drive or the response to CO2.